Reflexão sobre as políticas públicas educacionais para as diferenças surdas - Santos, Wesley Nascimento (Universidade Federal de São Carlos, 2023)
The implementation of Public Policies in Brazil is usually the result of many struggles that produce social achievements. These policies must guarantee the access of minority groups, specifically deaf people, to rights provided for in legal provisions. Thus, this work aimed to reflect on how educational public policies cover the specificities of deaf differences. Therefore, we researched how this construction of policies takes place, mainly when we think about the creation of laws and guidelines, considering or not the deaf differences. The power dispute ends up generating friction, as laws should be thought of for these people, noting that they are different lives, perspectives, discursive places and powers, however, in moments of debates for the creation of public policy, all deaf people are placed as a category only; thus, generating impasses and disputes of experiences; in an attempt to point out which needs more than the other. In order to carry out this study, a documentary and discursive analysis was carried out through videos available on public websites, about the inclusion of the Bilingual Education modality for the deaf as a regular teaching modality unrelated to Special Education. In this work, Deaf Studies and Cultural Studies were considered as our theoretical contribution. The importance of dialoguing with these deaf groups was observed, in order to better understand which public policy serves them. It is hoped that the present study will contribute to the reflection on the importance of having specific public policies to assist deaf subjects with their differences.
Reflection on public educational policies for deaf differenc
Keywords: Surdos; Legislação; Movimento social; Direitos humanos; Educação bilíngue de surdos; Diferenças surdas; Deaf; Legislation; Deaf signers; Social movement; Human rights; CIENCIAS HUMANAS::EDUCACAO::TOPICOS ESPECIFICOS DE EDUCACAO